Development of Thinking Computer Systems and Machine Learning in Health Care - Samuel C. (My University, 2025)
This chapter deals with artificial intelligence, machine learning, deep learning, and similar tools in health care management. The contents of the chapter are summarized as follows: The introduction section acquaints the reader with the role of machine learning and artificial intelligence in health care. Then a scanning of the related literature is presented. The past, present, and future of artificial intelligence in health care are components of the chapter. Innovative health care and personalized connected health care are also integral parts. Expert systems used in specific health care applications, regulatory models for artificial intelligence, and applications of machine learning for health care are also discussed. The challenges of having secure, private, and robust machine learning/deep learning for health care are addressed. Similarly, the challenges of artificial intelligence in health care are presented. Clinical decision support systems are discussed, as are ethical issues. Finally, future trends are also examined in the chapter. © 2022 selection and editorial matter, Vineet Kansal, Raju Ranjan, Sapna Sinha, Rajdev Tiwari, and Nilmini Wickramasinghe; individual chapters, the contributors.